Pengaruh Edukasi Gizi Terhadap Efikasi Diri Ibu Dalam Pemberian Makan Anak Balita - Maula Mar'atus Solikhah; Muhammad Seno Reynaldi; Octaviana Nursa’adah; Mutiaranika Sekarwangi; Rita Hadi Widyastuti Widyastuti5 (Jurnal Perawat Indonesia, 2025)
Abstract The nutritional intake in children is often not met due to several factors, one of which is the lack of self-efficacy of mothers in feeding their children. The results of a documentary study from the nutritional status report of the RW 4 Bulusan posyandu showed that 7.3% of children suffered from malnutrition. Parents stated that they did not have sufficient self-efficacy in providing the right food for their children, as in the practice of feeding, mothers tend to only prepare food that their children like. The purpose of this study was to determine the effect of nutrition education on the self-efficacy of mothers in feeding their children in RW 4 Bulusan, working area of Bulusan Health Center. The research method used was a quantitative method with a quasi-experimental research design (one group pre-test and post-test without control). The sample consisted of 32 respondents, taken by purposive sampling with inclusion and exclusion criteria. Data collection used a questionnaire on the self-efficacy of mothers in feeding. Data analysis was performed using a paired sample t-test. The results of the study showed that there was an effect of nutrition education on the self-efficacy of mothers in feeding their children, with a p-value <α (p-value = 0.000, α = 0.05). In conclusion, nutrition education is recommended to increase the self-efficacy of mothers in feeding their children.